2020
DOI: 10.3390/ijerph17207466
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Injury Severity Risk Factors in Fatal Crashes with Neural Network

Abstract: A better understanding of circumstances contributing to the severity outcome of traffic crashes is an important goal of road safety studies. An in-depth crash injury severity analysis is vital for the proactive implementation of appropriate mitigation strategies. This study proposes an improved feed-forward neural network (FFNN) model for predicting injury severity associated with individual crashes using three years (2017–2019) of crash data collected along 15 rural highways in the Kingdom of Saudi Arabia (KS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 103 publications
(118 reference statements)
0
7
0
Order By: Relevance
“…The situation analysis of the Road Safety Action Program examines that human-related issues cause most of the road accidents; thus, controlling them becomes the extremely dynamic goal of road safety actions [4][5][6]. Previous findings detected the human factors to be a primary or leading contributing cause in approximately 90% of road traffic crashes [7][8][9][10][11][12]. In addition, the study observed that driving behavior is one of the basic driver-related components that directly affect road safety [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The situation analysis of the Road Safety Action Program examines that human-related issues cause most of the road accidents; thus, controlling them becomes the extremely dynamic goal of road safety actions [4][5][6]. Previous findings detected the human factors to be a primary or leading contributing cause in approximately 90% of road traffic crashes [7][8][9][10][11][12]. In addition, the study observed that driving behavior is one of the basic driver-related components that directly affect road safety [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…given in ( 6) and randomized quantile residuals (qr) expressed in (7). Further, estimate the mean and standard error of the dr and qr.…”
Section: Algorithm For Charting Constantsmentioning
confidence: 99%
“…Injury Severity. So far, many research methods have been developed to investigate risk analysis and prediction in previous studies [15][16][17], and statistical regression approaches and methods based on machine learning (ML) have been the primary method on investigating the relationship between crash injury severity and risk factors [18,19]. For example, Xie et al developed a random-parameter ordered probit model to explore risk factors with crash severity on two-lane rural roads in China [20].…”
Section: Relevant Studies On the Modelling Approach For Crashmentioning
confidence: 99%